Differentiating Retirement Age to Compensate for Career Arduousness - Vincent Vandenberghe (Global Labor Organization (GLO), 2021)
Population ageing in Europe calls for an overall rise in the age of retirement. However, many argue that this age should be differentiated to account for individuals' career arduousness. This paper explores the relevance of this idea. It combines the 7th wave of the SHARE panel data on health at an older age and US occupational O*NET data. With these unique data it first quantifies the impact of entire career arduous- ness on health at typical retirement age, relative to other key determinants (gender, childhood health, parental longevity). It then estimates the degree of retirement age differentiation that would be needed to compensate individuals for their career-related health handicap/advantage and get closer to "real" actuarial fairness. Using the age of 65 as a reference, results point at the need for differentiation ranging from 60 to 71. But the paper also shows that systematic retirement age differentiation would fail to match a significant portion of the full distribution of health at an older age. In a world where retirement policy compensates for career-related arduousness there would still be a lot of unaccounted health differences; in particular those related to health endow- ment. Using variance decomposition methods, we estimate that career-arduousness represents at most 5.83% of the model-explained variance of health at an older age.
Keywords: J14; I1; J26; 330; Ageing; Health; Retirement Policy; SHARE; O*NET; Compensating Career Arduousness